Peradaban Islam: Masa Kebangkitan Kembali - Ella Anggraini; Nadia Putri Amanda NST; Syifa Salsabila; Radya Amalia; Rihla Azmira (Departement of Mathematics Education, 2023)
The purpose of this study is to find out that the Islamic Awakening in all fields is the result of renewal of thought in Islam. Modern Islamic revival takes the form of the popularity of various aspects of Islamic culture. One example is the development of Islamic clothing and many women who wear closed clothes but do not cover their curves. Islamic revival also does not. This shift in the concept of society is one of the important foundations of Islamic political history in the following centuries. Previously, in the tribal system, the bonding aspect of the community unit was blood and descent; In the concept of Ummah, the main binding aspect is religious belief (Islam). To regain the glory of Islam, Muslims must face internal and external struggles against the Western world. The revival of Islamic civilization with new enthusiasm shows that there is an Islamic transformation that never stops from time to time. This process was marked by the growth of Islamic institutions which were not only carried out by the government and Islamic organizations, but also by new Muslim groups that had existed before. On the socio-political stage itself, Islam has found momentum to emerge with its